Web Component Development with Zope 3 - Weitershausen, Philipp (Springer Berlin Heidelberg : Imprint: Springer, 2005)
New Zope 3 is a web applications server written in Python that allows developing complex web applications rapidly and collaboratively. Zope 3 is the successor to the successful version 2. After an introduction to the key concepts of Zope, a sample application is built and extended subsequently. The book is targeted towards developers familiar with the web and web technologies. Special sections for Zope 2 developers cover the basic differences to the predecessor. The concepts of Zope 3 and its component architecture are explained thoroughly, continually accompanied by a demo application.